Cultural Heritage and Identity in the Old Testament and the Implications for the Niger-Delta (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study examines the relationship between cultural heritage and identity as depicted in the Old Testament and its implications for the Niger Delta region of Nigeria. Drawing on biblical narratives that emphasize the preservation of cultural traditions, communal memory, and covenantal relationship, the research highlights how these elements sustained the Israelite community amid challenges that threatened their existence. The study contextualized these insights within the socio-political and environmental struggles faced by the Niger-Delta indigenous communities, who are confronted with threats to their cultural heritage and identity due to oil exploitation, environmental degradation, and political marginalization. This study employs a qualitative research method that integrates theological, literary, analytical, and phenomenological approaches. The findings reveal that revitalizing indigenous cultural heritage, shared communal values, and covenantal relationships can foster social cohesion, cultural continuity, and inspire resistance against any form of external assault and domination. By examining the Old Testament framework of cultural resilience, this research provides a cultural lens through which contemporary identity crises in the Niger Delta can be understood and addressed.